1971
DOI: 10.1111/j.1469-8137.1971.tb02573.x
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASTRUCTURAL CHANGES IN CHLOROPLASTS OF PHASEOLUS VULGARIS DURING DEVELOPMENT UNDER CONDITIONS OF NUTRIENT DEFICIENCY

Abstract: Summary Plants of Phaseolus vulgaris were grown for a period of 4 weeks in nutrient solutions deficient in S, Mg, K, N, P and Fe, and compared with controls growing in complete nutrient solutions. At weekly intervals, tissue from all leaf groups fully expanded at the time of sampling was prepared for examination under the electron microscope. It was possible to examine chloroplast ultrastructure, firstly, during leaf development under each of the nutrient deficient conditions and, secondly, to compare the chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
1

Year Published

1972
1972
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 30 publications
4
19
1
Order By: Relevance
“…Negative starch degradation process due to the absence of necessary degradative enzymes caused by nitrogen deficiency is assumed in these non-active chloroplasts. Similar studies in different plant species have been observed in this regard (Thomson and Weier, 1962;Whatley, 1971;Chonan et al, 1977), reflecting large starch grains in the chloroplasts of nitrogen deficient plants. In the present study, it seems that the size of chloroplast is directly affected by the continuous accumulation of starch grains.…”
Section: Discussionsupporting
confidence: 62%
“…Negative starch degradation process due to the absence of necessary degradative enzymes caused by nitrogen deficiency is assumed in these non-active chloroplasts. Similar studies in different plant species have been observed in this regard (Thomson and Weier, 1962;Whatley, 1971;Chonan et al, 1977), reflecting large starch grains in the chloroplasts of nitrogen deficient plants. In the present study, it seems that the size of chloroplast is directly affected by the continuous accumulation of starch grains.…”
Section: Discussionsupporting
confidence: 62%
“…16). With increasing age the lamellar alignment shows increasing distortion (Whatley, 1971a) and granal orientation becomes more varied, some grana being sectioned parallel to the face of the discs and others at right angles (Plate 3,No. 17).…”
Section: Stage XIImentioning
confidence: 99%
“…In cotton it diminished leaf size and stem elongation, protein and soluble sugars, and caused chlorosis (2). Chloroplasts contain proteins rich in S (4) and chloroplast morphology is considerably affected by S deficiency (3,8,16). Pirson (7) concluded that S deficiency upsets photosynthesis in a profound way which, after readdition of external sulfate, can only be corrected slowly through the synthesis of new protein and Chl.…”
mentioning
confidence: 99%
“…In cotton it diminished leaf size and stem elongation, protein and soluble sugars, and caused chlorosis (2). Chloroplasts contain proteins rich in S (4) and chloroplast morphology is considerably affected by S deficiency (3,8,16 …”
mentioning
confidence: 99%